Legal Study of Developer Responsibility for Bad Credit within the Framework of Law no. 1 of 2011 - Lorinza Hartomo Razy (International Journal of Law, Crime and Justice, 2024)
The development of housing credit provided by the North Lampung Matrix Housing Developer sometimes gives rise to bad credit problems, where the realization of the credit provided does not reach the predetermined target. This can affect North Lampung Matrix Housing activities and impact developer accountability. What is the developer's responsibility for credit in accordance with Law Number 1 of 2011 concerning Housing and Settlement Areas in Matrix Housing in North Lampung? The research results show that the developer's responsibility for credit in accordance with Law Number 1 of 2011 concerning Housing and Settlement Areas at Matrix Housing in North Lampung includes the obligation to collect debtors who experience problematic credit who collaborate with the developer. North Lampung Matrix Housing Partners Bank, basically this obligation has not been specifically regulated in the banking law and still uses general rules such as the Banking Law, Civil Code and Law Number 40 of 2007 concerning Limited Liability Companies. The absence of special "lex specialis" regulations is a weakness in responsibility when bad credit occurs. All components of North Lampung Matrix Housing have juridical responsibility for all operational activities. Resolving problem loans at Matrix Housing in North Lampung can be done in two ways, namely litigation efforts through the courts and non-litigation efforts through preventive measures such as anticipating the emergence of bad credit, early warning and negotiation.